Is Evangelicalism Now Politically Prophetic or Prophetically Political? Interrogating Clergy and ‘Politricks’ in the 21st Century - Patrick, Hosea Olayiwola; Ndlovu, James; Patrick, Rhoda Titilopemi Inioluwa; Akpan, Udoh James; Olasupo, Olusola (African journal of religion, philosophy and culture, 2025)
In the 21st century, the intersection of religion and politics in Africa has become increasingly pronounced, with clergy having an important effect on forming political landscapes. This paper explores whether evangelicalism is now politically prophetic or prophetically political by examining the influence of religious leaders on political outcomes. The distinction between being politically prophetic and prophetically political is subtle yet significant: the former aligns religious voices with specific political agendas, while the latter involves speaking truth to power regardless of political affiliations. Using Nigeria and Zimbabwe as case studies, this paper adopts a descriptive narrative framework and a qualitative desktop review approach. It draws on the Marxian theory to rationalise theocratic influence and followership dogma, suggesting that clergy involvement in politics serves elite interests and maintains the status quo. The paper argues that religious prophecies significantly impact political participation and voter behaviour, often leading to controversies and questions about the authenticity of these prophecies. The analysis highlights the dual roles of religious leaders as both spiritual guides and political influencers, raising important questions about the integrity of the prophetic voice in the realm of politics. The challenge lies in maintaining this integrity while engaging with the political realities of the 21st century. The paper concludes that while the intersection between interest, politics, and religion will continue to shape political participation, there is a need to ensure the integrity of the prophetic voice while engaging with present-day political realities.